A novel deep learning prognostic system improves survival predictions for stage III non‐small cell lung cancer. (2nd May 2022) - Yang, Linlin; Fan, Xinyu; Qin, Wenru; Xu, Yiyue; Zou, Bing; Fan, Bingjie; Wang, Shijiang; Dong, Taotao; Wang, Linlin
Abstract: Background: Accurate prognostic prediction plays a crucial role in the clinical setting. However, the TNM staging system fails to provide satisfactory individual survival prediction for stage III non‐small cell lung cancer (NSCLC). The performance of the deep learning network for survival prediction in stage III NSCLC has not been explored. Objectives: This study aimed to develop a deep learning‐based prognostic system that could achieve better predictive performance than the existing staging system for stage III NSCLC. Methods: In this study, a deep survival learning model (DSLM) for stage III NSCLC was developed based on the Surveillance, Epidemiology, and End Results (SEER) database and was independently tested with another external cohort from our institute. DSLM was compared with the Cox proportional hazard (CPH) and random survival forest (RSF) models. A new prognostic system for stage III NSCLC was also proposed based on the established deep learning model. Results: The study included 16, 613 patients with stage III NSCLC from the SEER database. DSLM showed the best performance in survival prediction, with a C‐index of 0.725 in the validation set, followed by RSF (0.688) and CPH (0.683). DSLM also showed C‐indices of 0.719 and 0.665 in the internal and real‐world external testing datasets, respectively. In addition, the new prognostic system based on DSLM (AUROC = 0.744) showed better performance than the TNM staging system (AUROC = 0.561). Conclusion: In this study, a new, integrated deep learning‐based prognostic model was developed and evaluated for stage III NSCLC. This novel approach may be valuable in improving patient stratification and potentially provide meaningful prognostic information that contributes to personalized therapy. Abstract : A newly integrated deep learning based prognostic model was developed and evaluated for stage III NSCLC, and was shown to have better performance than the TNM staging system. This novel approach may be valuable in improving patient stratification and potentially provide meaningful prognostic information that contributes to personalised therapy.